Advanced Water Treatment System of the Bureau of Waterworks, Tokyo Metropolitan Government. (4th July 2019) - Yoshizawa, Kenichi
ABSTRACT: Since 1992, the Bureau of Waterworks, Tokyo Metropolitan Government (BWT) has introduced the advanced water treatment process, which is composed of ozonation and biological activated carbon treatment, within its service areas in a phased manner. The entire amount of water from the Tone River system has been treated by the advanced water treatment since 2014. The BWT currently has a capacity to treat approximately 5.5 million m 3 per day using the advanced water treatment process. This report describes the progress of advanced water treatment facilities, the ozonation method, and the characteristic ozone diffusion devices used in Tokyo.